2018
DOI: 10.1111/are.13669
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth, feed utilization efficiency and immune parameters in tiger shrimp (Penaeus monodon) fed diets supplemented with or diet fermented with gut bacteriumBacillussp. DDKRC1. isolated from gut of Asian seabass (Lates calcarifer)

Abstract: Evaluation of growth, feed utilization efficiency and immune parameters in tiger shrimp (Penaeus monodon) fed diets supplemented with or diet fermented with gut bacterium Bacillus sp. DDKRC1. isolated from gut of Asian seabass (Lates calcarifer) SummaryAn experiment was conducted to assess the effect of supplementation of cellulolytic gut bacterium with plant protein-based diet on growth, digestibility and digestive enzyme status of tiger shrimp, Penaeus monodon. Bacillus sp. DDKRC1. (JN641289), a potential ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…Nevertheless quantitatively the total substrate solid or biomass developed in the form of periphyton did not differ significantly between bamboo substrate integrated biofloc (F + B) and Bamboo mat (B) group; the carbohydrate supplementation improved the quantity and diversity of the microbial community like total microbial count, Bacillus and Lactobacillus and yeast counts over the bamboo mat in F + B group. Higher secretion of digestive enzymes by many of the probiotic bacteria and yeast might have attributed to the growth performance, survival, and immune indicators in these groups (De, Ananda, Ghoshal, Mukherjee, & Vijayan, ; Farzanfar, ; Rengpipat et al, ; Zheng & Wang, ; Ziaei‐Nejad et al, ). Further, the provision of the substrate increased the surface area of the tank by 75.0% which in turn effectively reduced the relative stocking density which appears to reduce the stress level in shrimp (Schveitzer et al, ) and improved shrimp survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless quantitatively the total substrate solid or biomass developed in the form of periphyton did not differ significantly between bamboo substrate integrated biofloc (F + B) and Bamboo mat (B) group; the carbohydrate supplementation improved the quantity and diversity of the microbial community like total microbial count, Bacillus and Lactobacillus and yeast counts over the bamboo mat in F + B group. Higher secretion of digestive enzymes by many of the probiotic bacteria and yeast might have attributed to the growth performance, survival, and immune indicators in these groups (De, Ananda, Ghoshal, Mukherjee, & Vijayan, ; Farzanfar, ; Rengpipat et al, ; Zheng & Wang, ; Ziaei‐Nejad et al, ). Further, the provision of the substrate increased the surface area of the tank by 75.0% which in turn effectively reduced the relative stocking density which appears to reduce the stress level in shrimp (Schveitzer et al, ) and improved shrimp survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The phenol oxidase enzyme causes inactivation of foreign cells through melanization and prevent their spread throughout the body (Amparyup, Charoensapsri, & Tassanakajon, ). It has been reported that bacterial cell wall components such as lipopolysaccharide (LPS), β‐1, 3 glucans and microalgal products enhance total hemocyte count and proPO activity in shrimp (Campa‐Córdova, Hernández‐Saavedra, De Philippis, & Ascencio, ; De et al, ; Ringo, Jose, Vecino, Wadsworth, & Song, ). As both periphyton and biofloc are primarily a microbial consortium developed in the form of biofilm over the bamboo mat, the best immune response in bamboo mat integrated biofloc (F + B) system is evident.…”
Section: Discussionmentioning
confidence: 99%
“…are important because of their ability to produce antibiotics/metabolites which have antagonistic effects against pathogenic microorganisms ( Sun et al, 2010 ; Abarike et al, 2018 ; Kuebutornye et al, 2019 ). Literatures have proven that aquaculture animals with diet supplemented with Bacillus species as probiotics resulted in a better protein efficiency ratio, lower feed conversion ratio, and fast growth ( De et al, 2018 ; Goda et al, 2018 ; Sadat Hoseini Madani et al, 2018 ). Nimrat et al (2012) also reported that forms of Bacillus probiotics and modes of probiotic administration Bacillus probiotics did not affect the growth and survival of shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on Bacillus spp. focused on the use of single culture ( Zokaeifar et al, 2014 ; Barman et al, 2018 ; De et al, 2018 ), while it is largely speculative whether two or even multiple combinations of strains/species would be beneficial. Reportedly, multi-strain/specie probiotics also enhanced protection against pathogenic infection ( Timmerman et al, 2004 ; Kesarcodi-Watson et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fermented dragon fruit in the diet improves the growth performance and feed utilization of Platax pinnatus and increases antioxidant enzyme activity to some extent (Chu et al, 2021). Feeding fermented feed by Bacillus subtilis to Penaeus monodon is shown to improve the growth performance, feed digestibility, survival rate and immunity of spot prawns (De et al, 2018).…”
Section: Introductionmentioning
confidence: 99%